Head first jQuery - Benedetti, Ryan.; Cranley, Ronan (Sebastopol, CA : O'Reilly Media, 2011)
This book explains how to build complex scripting functionality with minimal coding, providing coverage of functions ranging from incorporating Ajax apps and overcoming the limits of HTML and CSS to building plug-ins and using animation.
Includes index.
rua 21/10/13
Loans
Keywords: JavaScript (computer program language); Ajax (web site development technology); Web sites; jquery